Variation in the Abundance of Neotropical Bees in an Unpredictable Seasonal Environment - Knoll, F. R.N. [UNESP] (Springer Nature, 2016)
This study provides information on the number of orchid bees based on a long-term monitoring study in an antropized savanna region in Southeastern Brazil. Sampling was carried out using chemical lures, and 77 samples were monthly collected to assess the number of individuals as well as the annual and seasonal species fluctuation. The number of species varied significantly among years but not among months, and there was a positive correlation between the number of species and the number of individuals in each sample. Monthly number counts revealed a seasonal pattern for Eulaema nigrita Lepeletier and Exaerete smaragdina Perty, which were more numerous during humid months but peaked in December, January, and February. Different species of Euglossa presented a significant variation in number among years, but not among months, with no pattern along the years. The community and the populations studied were less stable when compared to those of well-preserved habitats of equatorial forests. The El Niño phenomenon of 1997/98 did not result in negative effects in the populations studied; on the contrary, there was a peak in the number of E. nigrita. The amplitude in the yearly variation of the male orchid bee population reflects the evolutionary history of species living in unpredictable seasonal weather that led to the development of particular adaptive traits designed to deal with environmental uncertainties. This study suggests that the plasticity of the life cycle may explain population stability and provide greater resilience to severe climate change events in the future.
Keywords: El Niño; ENSO; long-term sampling; orchid bees; seasonality; stability index